1999
DOI: 10.1088/0953-8984/11/48/302
|View full text |Cite
|
Sign up to set email alerts
|

First-principles theory of ultrathin magnetic films

Abstract: We report on a set of systematic first-principles electronic structure investigations of the magnetic spin moments, the magnetic spin configurations, and the magnetic coupling of ultrathin magnetic films on (001)- and (111)-oriented noble-metal substrates and on the Fe(001) substrate. Magnetism is found for 3d-, 4d-, and 5d-transition-metal monolayers on noble-metal substrates. For V, Cr, and Mn on (001) substrates a c(2 × 2) antiferromagnetic superstructure has the lowest energy, and Fe, Co, Ni are ferromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 81 publications
(81 reference statements)
8
27
2
Order By: Relevance
“…The same method was used very successfully in the past 20 to predict the STM images of Fe surfaces. In this calculation the surface was modeled by a 31-layer film which is sufficient to have a good approximation of the surface, and more important minimize the influence of spurious size quantization effects which are present in finite-size slab calculations.…”
Section: Calculational Methodsmentioning
confidence: 99%
“…The same method was used very successfully in the past 20 to predict the STM images of Fe surfaces. In this calculation the surface was modeled by a 31-layer film which is sufficient to have a good approximation of the surface, and more important minimize the influence of spurious size quantization effects which are present in finite-size slab calculations.…”
Section: Calculational Methodsmentioning
confidence: 99%
“…Mainly the weakly interacting coinage metals (Cu, Ag, Au) and some transition metals (TMs), for example, Pd, have been chosen as substrates in order to minimize the interaction between monolayer and substrate. 1,2 Cu with an experimental lattice constant of a 0 = 3.61Å turned out to be an ideal template for fcc bulk TMs, while Ag (a 0 = 4.09Å) and Au (a 0 = 4.08Å) are templates to grow bcc metals. Employing density functional theory (DFT), some general trends were identified for 3d monolayers (MLs) on these substrates: (i) The magnetic moments of the monolayers are considerably enhanced as compared to the equivalent bulk systems and, (ii) similar to the bulk cases, Fe, Co, and Ni are ferromagnetic (FM) on these substrates, while V, Cr, and Mn prefer a c(2 × 2) antiferromagnetic (AFM) structure (i.e., a checkerboard arrangement of antiparallel magnetic moments, 3,4 ) a magnetic structure that cannot be derived from respective bulk phases.…”
Section: Introductionmentioning
confidence: 98%
“…͑The spin susceptibility of V favors an AF ground state for large volumes. Since this early calculation was restricted to FM solutions, the AF state 3 was not found for the enlarged volumes.͒ Magnetism was reported for V monolayers ͑ML͒ on magnetic and nonmagnetic substrates [4][5][6][7] and thin films on Fe͑001͒. [8][9][10][11][12][13][14] Indeed, early calculations [15][16][17] suggested that the V͑001͒ surface might also be magnetic and experimental investigation with electron capture spectroscopy by Rau et al 18 seemed to confirm these findings.…”
Section: Introductionmentioning
confidence: 99%